Does Situation-Specificity Affect the Operation of Implementation Intentions?. Issue 6 (November 2017) - Epton, Tracy; Armitage, Christopher J.
Abstract: Interventions that encourage people to link critical situations with appropriate responses (i.e., "implementation intentions") show promise in increasing physical activity. The study tested whether implementation intentions designed to deal with generic situations are more effective than implementation intentions designed to respond to specific situations. One hundred thirty-three participants either: (a) formed implementation intentions using a volitional help sheet with 10 critical situations (i.e., standard volitional help sheet); (b) formed implementation intentions using a volitional help sheet with one generic situation (i.e., single situation volitional help sheet); or (c) did not form implementation intentions (i.e., control condition). Participants who formed implementation intentions reported more physical activity and greater self-regulation than those in the control condition. There were no differences between participants who were provided with one generic critical situation and those who were provided with 10 specific critical situations. Implementation intentions successfully increased self-reported physical activity irrespective of critical situation specificity. The implication is that implementation intention-based interventions are robust and require minimal tailoring. Highlights: Increased physical activity has a positive health benefit Two interventions were compared against a control in increasing physical activity The interventions increased vigorous physical activity in particular The brief intervention was as effective as the standard intervention